Weird Wolf - Cuyler, Margery (New York, NY, 1989)
Summary: When Harry Walpole discovers he is a werewolf, his attempts to break the curse are unsuccessful until he is aided by his pushy friend Abby.
Keywords: Werewolves; Fiction